Influence of Optic Nerve Appearance on Visual Outcome in Pediatric Idiopathic Intracranial Hypertension. (4th September 2020) - Micieli, Jonathan A.; Bruce, Beau B.; Vasseneix, Caroline; Blanch, Richard J.; Berezovsky, Damian E.; Newman, Nancy J.; Biousse, Valérie; Peragallo, Jason H.
ABSTRACT: Objectives : To determine whether optic disc hemorrhages (ODH) and cotton wool spots (CWS) at presentation are associated with worse visual outcomes in pediatric patients with idiopathic intracranial hypertension (IIH). Methods: : Retrospective institutional review of 100 eyes of 50 consecutive pediatric IIH patients (aged 16 years or less) who had baseline optic disc photographs before or within 30 days of their diagnostic lumbar puncture and initiation of medical treatment. Optic disc photographs were independently graded by three ophthalmologists in a standardized manner. Visual function was assessed using visual acuity (VA) and visual field grade (VFG). Results: At least one ODH was found in 41% of eyes, at least one CWS was found in 27% of eyes, and 20% of eyes had both ODH and CWS. At presentation, Frisén grade was associated with the presence of CWS ( p = 0.013) and showed no association with ODH ( p = 0.060). When controlling for Frisén grade, ODH and CWS were not associated with worse VA or VFG at final follow-up. Severe ODH were associated with worse VA and VFG at presentation ( p < 0.03), but not at final follow-up. Severe CWS at presentation was strongly associated with a worse Humphrey mean deviation of 5.0 dB (95% confidence interval 1.6–8.3) at final follow-up ( p = 0.002). Conclusion: When controlling for the severity of papilledema, ODH do not provide any additional prognostic value in pediatric IIH patients. Frisén grade and severe CWS at presentation were independently associated with worse visual outcomes at the final follow-up.